2012
DOI: 10.1161/atvbaha.111.226845
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neutrophil Function by Adenosine

Abstract: Adenosine is an endogenously released purine nucleoside that signals via 4 widely expressed G protein-coupled receptors: A 1 , A 2A , A 2B , and A 3 . In the setting of inflammation, the generation and release of adenosine is greatly enhanced. Neutrophils play an important role in host defense against invading pathogens and are the cellular hallmark of acute inflammation. Neutrophils both release adenosine and can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
235
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(254 citation statements)
references
References 90 publications
4
235
0
6
Order By: Relevance
“…receptors [57]. In addition, neutrophil-derived TNF-α has been shown to contribute to the amplification of IL-6 production by human neutrophils stimulated by a TLR8 ligand [58].…”
Section: Other Paracrine Amplification Mechanismsmentioning
confidence: 99%
“…receptors [57]. In addition, neutrophil-derived TNF-α has been shown to contribute to the amplification of IL-6 production by human neutrophils stimulated by a TLR8 ligand [58].…”
Section: Other Paracrine Amplification Mechanismsmentioning
confidence: 99%
“…As discussed above, the A 2B R is a G s -coupled protein receptor, which activates adenylyl cyclase and increases cAMP production; thus, this serves as a positive feedback mechanism wherein A 2B R increases its own expression and promotes renal fibrosis in the setting of hypoxia. Importantly, bone marrowderived cells involved in inflammation seen in early hypoxia co-express A 2A R and A 2B R; however, A 2A R has a much greater affinity for adenosine; thus, its effects likely predominate under physiologic conditions [57]. Under pathologic conditions, such as hyperglycemia and buildup of angiotensin II, local levels of adenosine increase and promote fibrosis by activation of A 2B R on mesangial cells and fibroblasts.…”
Section: Unique Aspects Of Adenosine Receptor Signaling In Organ Fibrmentioning
confidence: 99%
“…Unlike the brief changes in tissue levels created by exogenously administered adenosine22 or adenosine‐receptor agonists,23 MSCs are capable of continuously and rapidly metabolizing ATP and AMP to adenosine by the actions of surface membrane ecto‐5′‐nucleotidases CD39 and CD73, respectively 24, 25, 26. Increased bioavailability of adenosine may subsequently favor an anti‐inflammatory microenvironment that mitigates the destructive potential of the innate immune response 24, 25, 26, 27. We found that implanted MSCs increase adenosine bioavailability through the action of CD73 and that this mechanism is critical to reducing early innate immune cell infiltration and ROS formation while protecting cardiac function following MI/R injury.…”
Section: Introductionmentioning
confidence: 99%